A Review of Selected Solutions on the Evaluation of Coal-Rock Cutting Performances of Shearer Picks under Complex Geological Conditions - Linlin Wang; Dekun Zhang; Dagang Wang; Cunao Feng (Applied Sciences, 2022)
During automatic and intelligent cutting at the coal mining face, complex geological conditions (fold structure, fault structure and magmatic intrusion) easily cause distinct occurrence conditions of coal rock seams (gangue, inclusion, or fault in the coal and rock), which induces different coal-rock cutting performances of shearer picks. Therefore, the objective of the present study is to review the selected solutions on the evaluation of coal-rock cutting performances of shearer picks under complex geological conditions. Occurrence conditions of coal rock seams were classified according to different criteria. Mechanical coal-rock breakage of coal rock by shearer picks were introduced. Shearer pick forces during coal-rock cutting (load spectrums of the pick and the mechanical model of the pick force) and coal-rock cutting mechanism (coal-rock cutting process by the pick and pick failure mechanisms) were discussed. The service safety evaluation of the pick based on wear and fatigue (pick wear, quantitative evaluation of service safety, and methods to improve the service safety) was presented. Finally, research prospects were outlined to propose the future research focus of shearer picks under complex geological conditions, such as the adaptive cutting of shearers, the fusion detection method of coal-rock interface by automatic shearers, the effects of geological conditions on coal-rock cutting mechanisms, the selection of systems suitable for different geological conditions, and shearer pick reliability evaluation. Results of this study are of great significance in understanding failure modes and the cutting mechanisms of shearer picks, quantitatively evaluating pick safety, promoting the automatic and intelligent cutting of coal rock seams, and thereby improving the production efficiency of shearers.